1996
DOI: 10.1007/bf00376507
|View full text |Cite
|
Sign up to set email alerts
|

Change in sympathetic activity, cardiovascular functions and plasma hormone concentrations due to cold water immersion in men

Abstract: The purpose of this study was to determine whether or not repeated short-term cold water immersions can induce a change in the activity of the sympathetic nervous system and, consequently, in cardiovascular functions in healthy young athletes. Changes in some plasma hormone concentrations were also followed. A single cold water immersion (head-out, at 14 degrees C, for 1 h) increased sympathetic nervous system activity, as evidenced by a four-fold increase (P < 0.05) in plasma noradrenaline concentration. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
0
37
2
1
Order By: Relevance
“…The difference between the first (autumn) and third (spring) measurements was on average 6 mmHg, which is in accordance with the drop in catechol values and can be regarded as a sign of adaptation to repeated cold exposure or the research protocol. Diastolic pressure did not change in our material, but in a long distance cold water (10-14 o C) swimming experiment diastolic pressure was lowered on the fourth day (11). Some winter swimmers have reported that swimming without any medication, has lowered their elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 49%
“…The difference between the first (autumn) and third (spring) measurements was on average 6 mmHg, which is in accordance with the drop in catechol values and can be regarded as a sign of adaptation to repeated cold exposure or the research protocol. Diastolic pressure did not change in our material, but in a long distance cold water (10-14 o C) swimming experiment diastolic pressure was lowered on the fourth day (11). Some winter swimmers have reported that swimming without any medication, has lowered their elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 49%
“…While acclimatization has some cardiorespiratory effects it does not appear to have a major effect on thermal status, which is also the case for plasma renin-angiotensin activity and aldosterone concentrations (181). Chronic HOWI in 10 • C to 4 • C water for three months resulted in decreased catecholamine response to cold HOWI (174).…”
Section: Acclimatizationmentioning
confidence: 97%
“…These data suggest that in addition to physiological responses to WI per se, cold WI specifically, increases SNA (357). HOWI for one hour in 14 • C water increased SNA, as indicated by a fourfold increase in plasma NE, but not epinephrine or dopamine (180,181).…”
Section: Head-out Water Immersion In Cold Watermentioning
confidence: 98%
“…Ice-cold water also has an effect in the positive response of the immune system (12)(13)(14)(15)31). exposure of the human body to various temperatures (cold and warm) is not limited only to immuno-endocrine response, in that changes on the body surface may also be observed.…”
mentioning
confidence: 99%
“…Various forms of thermal stimulation with the use of a cold temperature are differentiated in the academic literature. that most often applied and described is cryostimulation -local or general (cryochamber) with the use of nitrogen vapour or carbon dioxide at temperatures of from -60°c to -160°c at up to three minutes in length (2,4,8,9,12,(22)(23)(24)(25)28). In the stimulation defined as cold water immersion (cwM) water at a temperature of from 8°c to 15°c is used.…”
mentioning
confidence: 99%